2017
DOI: 10.4103/2045-9912.208521
|View full text |Cite
|
Sign up to set email alerts
|

Subacute normobaric oxygen and hyperbaric oxygen therapy in drowning, reversal of brain volume loss: a case report

Abstract: A 2-year-old girl experienced cardiac arrest after cold water drowning. Magnetic resonance imaging (MRI) showed deep gray matter injury on day 4 and cerebral atrophy with gray and white matter loss on day 32. Patient had no speech, gait, or responsiveness to commands on day 48 at hospital discharge. She received normobaric 100% oxygen treatment (2 L/minute for 45 minutes by nasal cannula, twice/day) since day 56 and then hyperbaric oxygen treatment (HBOT) at 1.3 atmosphere absolute (131.7 kPa) air/45 minutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Patients with chronic obstructive pulmonary disease that can cause reduced oxygen supply to the brain have shown GMV reduction in widespread regions, including the frontal cortex, the cingulate cortex, and other subcortical regions ( Zhang et al, 2013 ). A two-year-old girl who suffered from water drowning demonstrated GMV atrophy in temporal, parietal, and cerebellar lobes, and the GMV atrophy was dramatically improved after receiving oxygen therapy ( Harch and Fogarty 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic obstructive pulmonary disease that can cause reduced oxygen supply to the brain have shown GMV reduction in widespread regions, including the frontal cortex, the cingulate cortex, and other subcortical regions ( Zhang et al, 2013 ). A two-year-old girl who suffered from water drowning demonstrated GMV atrophy in temporal, parietal, and cerebellar lobes, and the GMV atrophy was dramatically improved after receiving oxygen therapy ( Harch and Fogarty 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not include a control group of patients with non-COVID-19 pneumonia, a condition that may lead to GMV alterations in several brain regions due to the decreased oxygenation to the cortex ( Zhang et al, 2013 ; Harch and Fogarty, 2017 ). Future work should address these potential confounding factors and aim to elucidate whether the lack of adequate brain oxygenation rather than direct inflammatory/viral-triggered processes are responsible for neurodegenerative processes in this patient population.…”
Section: Limitationmentioning
confidence: 99%
“…The use of hyperbaric air as a placebo is energetically debated and controversial because it increases the oxygen tension. In contrast to the placebo findings, similar published studies not using the hyperbaric air placebo, found significant improvements in brain injury ( 10–20 ).…”
Section: Introductionmentioning
confidence: 67%